3D Printed Graphene Based Supercapacitors - Costa, Guilherme Cadete Paixão da (2020)
This thesis aims to develop graphene-based supercapacitors. There is an emerging interest in the development of lightweight, high capacity and high durability supercapacitors. As the electronic equipment are getting lighter and lighter but simultaneously requiring more power supply, the energy density of batteries and/or supercapacitors should respond to this demand. Therefore, graphene-based supercapacitors have been investigated as potential material for high capacity power sources. The graphene is a very light material and has a huge surface area together with high conductivity, thus it is ideal for charge accumulation. In this work graphene was obtained by electrochemical exfoliation as a greener and harmless technique when compared to Hummer’s method. Two rods of graphite we used as electrodes for electrochemical exfoliation in a bath of H2SO4 , being studied the influence of acid concentration and applied potential on the graphite/graphene powder quality. That was evaluated by XRD, SEM and micro Raman spectroscopy. The obtained graphene-oxide powder was mixed with a polymeric binder agent and then used to print electrodes. The conductive of electrodes was optimized with a thermal treatment around 350ºC in different atmospheres. The performances of supercapacitors were tested for two different geometries, vertical (sandwich type) and planar (inter-digital configuration). These devices were studied for their stability and capacitance by CV curves and electrochemical impedance spectroscopy. This work proves that it is possible to use graphene-oxide powder, produced via electrochemical exfoliation, to make 3D printable inks for supercapacitors applications.